Rethinking the diagnosis of primary progressive aphasia: current challenges and future directions - Macoir, Joël; Lavoie, Monica; Duboisdindien, Guillaume; Laforce, Robert (Frontiers in Aging Neuroscience, 2025)
Primary progressive aphasia (PPA) is a clinical syndrome characterized by the progressive decline of language abilities due to neurodegenerative disease. Accurate and timely diagnosis is critical for effective clinical management, patient support, and research participation. However, several diagnostic challenges persist, including limitations in current syndromic classifications, lack of linguistically and culturally standardized assessment tools, overlap with other neurocognitive disorders, heterogeneity in underlying pathology, limited biomarker specificity, and unequal access to specialized care. This article reviews key diagnostic barriers and proposes future directions to improve the clinical identification and classification of PPA, with an emphasis on cross-linguistic and cross-cultural considerations.